Experimental determination of the solubility product of dolomite at 50–253 °C. (1st March 2018) - Bénézeth, Pascale; Berninger, Ulf-Niklas; Bovet, Nicolas; Schott, Jacques; Oelkers, Eric H.
Abstract: The 'dolomite problem', the scarcity of present-day dolomite formation near the Earth's surface, has attracted much attention over the past century. Solving this problem requires having reliable data on the stability and kinetics of formation of this mineral. Toward this goal, the solubility of natural dolomite (CaMg(CO3 )2 ) has been measured from 50 to 253 °C in 0.1 mol/kg NaCl solutions using a hydrogen electrode concentration cell (HECC). The obtained apparent solubility products ( K app-sp-dol ), for the reaction: CaMg(CO3 )2 = Ca 2+ + Mg 2+ + 2CO3 2−, were extrapolated to infinite dilution to generate the solubility product constants for this reaction ( K sp°-dol ). The derived equilibrium constants were fit and can be accurately described by log10 K sp°-dol = a + b / T (K) + cT (K) where a = 17.502, b = −4220.119 and c = −0.0689. This equation and its first and second derivatives with respect to T were used together with corresponding aqueous species properties to calculate the revised standard state thermodynamic properties of dolomite at 25 °C and 1 bar, yielding a Gibbs energy of formation ( Δ f G 298.15 ∘ ) equal to −2160.9 ± 2 kJ/mol, (log10 K sp°-dol = −17.19 ± 0.3); an enthalpy of formation ( Δ f H 298.15 ∘ ) of −2323.1 ± 2 kJ/mol, an entropy ( S 298.15 ∘ ) of 156.9 ± 2 J/mol/K and heat capacity ( C p 298.15 ∘ ) of 154.2 ± 2 J/mol/K (uncertainties are 3 σ ). The dolomite solubility product derived in this study is nearly identical to that computed using SUPCRT92 (Johnson et al., 1992) at 200 °C, but about one order of magnitude higher at 50 and 25 °C, suggesting that dolomite may be somewhat less stable than previously assumed at ambient temperatures.